Digestibility of feed ingredients in Florida pompano, Trachinotus carolinus adapted to either sea water or low salinity. (5th April 2016) - Riche, M.; Barrows, F.T.; Gaylord, T.G.
Abstract: Seven potential feed ingredients were evaluated for digestibility with Florida pompano Trachinotus carolinus using extruded diets. Ingredients included Special Select ™ menhaden meal, fishery processing by‐product (Montlake meal), NuPro ® yeast extract, canola protein concentrate, corn protein concentrate, barley protein concentrate and Spirulina. Digestibility values were determined when fish were held at 3 and 28 g L −1 salinity to determine the effect of salinity on digestibility. With the exception of the canola protein concentrate, the coefficients were numerically higher in pompano held at 28 g L −1 . No significant differences were detected for apparent crude protein or apparent energy digestibility between the two salinities. Amino acids were highly available from the two marine‐based ingredients and the barley and canola concentrates. The availability of alanine, leucine, isoleucine and phenylalanine was significantly higher ( P < 0.05) from the barley protein concentrate at 28 g L −1 than 3 g L −1 salinity. Methionine and phenylalanine were highly available from all the ingredients except the yeast protein. Conversely, glycine was not well utilised from any of the ingredients. The apparent digestibility coefficients provided here allow for more precise formulation of diets for Florida pompano reared in both seawater and low‐salinity environments.